Optimization of the environmental protection tax system design based on artificial intelligence - Zhang, Jing (Frontiers in Environmental Science, 2023)
China achieved significant economic growth in the past two decades, the sustained economic growth also brings negative implications environment. Chinese government has introduced various fiscal reforms to mitigate the negative implication of environment in the economy. Modernization of China's governance system and improvement of social development was the main goal of the 14th Five-Year Plan. The ecological environmental governance system is the main part of the country's governance system. Artificial intelligence promotes efficiency of bonded governance environment and boosts national management modernization. This paper analyzes the existing problems of Environmental Protection Tax from the perspective of literature review and tax principles and discusses the construction of Environmental Protection Tax System based on artificial intelligence. This paper suggests that the artificial intelligence construction of Environmental Protection Tax System improves Tax Collection and Management, Tax Payment Service and Tax Management. Besides, the government should adopt other strategies to promote clean environment, such as tax exemption for green and cleaner production. Provide easy loans to the exports, especially those contributing to clean energy production.